Kesulitan Siswa dalam Menulis Aksara Sunda - Suli Mariam; Elly Sukmanasa; Rini Sri Indriani (Ideas Publishing, 2026)
Students have difficulty writing Sundanese characters such as writing the swara script, the ngalagena script, the rarangkén and the numeric characters. So this study aims to analyze the difficulties of students in writing Sundanese script in one of the V-B grade students at Pondok Rumput State Elementary School. This research was conducted using a descriptive analytical qualitative research approach. In practice, the data collection and recording techniques used by researchers are triangulation of combining information between observations, interviews and documentation. Checking and checking the validity of the data using the data trust test (credibility), transferability test, dependability test, confirmability test. This research was conducted in the Even Semester of the 2019/2020 Academic Year. The results of the research obtained from students, teachers and parents showed that the students under study experienced obstacles when writing Sundanese characters which came from many factors so that it was difficult to write Sundanese characters properly and correctly according to predetermined rules. Based on the results of the above research, the researcher concluded that students experienced difficulties in writing Sundanese script due to several factors including lack of understanding of Sundanese script material, difficulty memorizing Sundanese script symbols, students' concentration was easily distracted when learning to write Sundanese characters so that students tended to find it difficult to understand the material. learning, it is easy to forget about learning and get unsatisfactory results. In addition, students are less interested in learning Sundanese script material, so students are not active in asking questions, it is difficult to conclude learning outcomes and are not timely in collecting assignments and learning methods / teaching methods that teachers often do when the learning process is monotonous and boring.